CONCEPT OF R-12 AND R-47 IN NEGATION SENTENCE WITH PLURAL 12 ON HAHSLM 472319 IN ECONOMIC COVID ERA - A, R Mochamad (Proceeding of International Conference on Islamic Education (ICIED); Vol 6 No 1 (2021): Proceeding of International Conference on Islamic Education (ICEID), 2021)
The purpose of this study is to analyze the concept Of R-12 and R-47 with negation sentence by Quran 51.56 that has worship first then human according to the constant 12 and the formula of hahslm 472319 in the economic age of covid. These research objects are the holy book and formulas of R-12 and R-47. Research is studied through a search of books, journals, holy books, and other electronic media. The methodology used is analytical descriptive in analogies and negatory sentences in Indonesian grammar. The method employed is the similarity and reflexivity of the hahslm 472319. The result is the analogy of R-12 as worship before R-47 as the universe in the form of paying for food versus eating-paying. The mirroring system also corresponds to a projector paradigm consisting of the notebook, projector, and screen. The mirror's position consisted of shadow, mirror, and people. The blueprint presence is a reflective reflection of the 12 constants stored from the Quran 51.56 verse number (1+5) times (5+6) root of digit 2 becomes 6x2=12. This constancy of the twelve reflects 1 salat Subuh and 2 salat Jamak (dzuhur asar and magrib isa). The conclusion is that the subject, I, in the negation sentence, did not create humans first then humans order to worship. But I, first made the design of worship, then continue with creating humans. These God words are the same with RPS as blueprint of course semester content. This RPS also can adapt with economic covid age.